Relationships of between single-leg standing up ability, hip/knee flexion angles during single-leg landing, and knee muscle strength - Kamiike, K; Onishi, S; Yoshiya, S; Kawaguchi, K (Japanese Journal of Clinical Sports Medicine, 2023)
The purpose of this study was to investigate the relationships between the single-leg standing-up test（SLST）, hip/knee flexion angles during single-leg landing and knee muscle strength. Sixty-five subjects with out any orthopaedic symptoms were included in the study. The subjects were classified into higher and lower SLST ability groups depending on whether they could perform SLST from the 20cm level. For the kinematic analysis of landing, single-leg landing motion from a 30cm high platform was videotaped from the lateral side.Markers were attached to bony landmarks in the pelvis and lower limbs, and knee and hip flexion angles were measured on the video image. Isometric knee extensor and flexor strength were also evaluated. During the data analysis, the obtained results were compared between the groups. The comparative analyses showed that the hip and knee flexion angles on landing were significantly larger and the knee flexor strength was significantly greater in the group exhibiting higher SLST ability. These results suggest that larger hip and knee joint flexion angles on single-leg landing and higher knee flexor strength are associated with superior performance in the SLST.